FORMULATION DEVELOPMENT OF GUMMY COMPRISING GINGER (Zingiber officinale), CURCUMA (Curcuma xanthorrhiza), AND LEMONGRASS (Cymbopogon citratus) (Universitas Muhammadiyah Yogyakarta, 2025)
Ginger (Zingiber officinale), Curcuma (Curcuma xanthorriza), and lemongrass (Cymbopogon citratus) are herbal plants widely known by the public to maintain health for various ages, including children. Even though they are beneficial, children tend to find it challenging to accept herbs because of their bitter taste. A method that can reduce the bitter taste of herbs is to prepare them into a gummy. Therefore, this study aimed to formulate those herbal plant extracts into gummy using gelatin. The gummy manufacturing method involved heating, mixing, filtering, molding, and cooling. Due to the Curcuma pH stability, citric acid or tamarind was used as the acid source. Several tests were carried out to ensure the safety and quality of the gummy. They are organoleptic tests, weight uniformity, dimension uniformity, determination of water content, microbial contamination tests, and metal contamination tests. The results show that the gummy formulation meets the organoleptic requirements, weight uniformity, and the dimensions of the gummy.